Perancangan Sistem Informasi Pada TK Al-Fairuz Berbasis Web - Muhammad Bahrul Alam (Journal of Research and Publication Innovation, 2023)
Al-Fairuz Kindergarten is one of the education industries, the problem that exists in this Kindergarten is that when carrying out promotions and data processing it still uses manuals then the resulting data is still in the form of manual recording and not uses Ms. Office Excel, then the results are used to input student data. In this ever-evolving digital era, an effective and efficient information system is needed. With these problems an Information System will be designed at the Web-Based Al-Fairuz Kindergarten. The research method used in the development of information systems, there are several methods that are commonly used, including observation, interviews, literature study, system analysis, and system design. These methods form the basis for building an effective and efficient information system. In addition, in its implementation, a programming language is used as a tool to develop the information system using the programming language PHP, MySQL, HTML, CSS, and the waterfall method. Based on the analysis, planning, implementation, and discussion that has been carried out in creating the tk al-fairuz website, it can be concluded that the tk al-fairuz Information System is expected to help the promotion and registration process to be efficient and effective. The tk al-fairuz website can make it easier to get to know the tk al-fairuz school. The tk al-fairuz information system is also expected to be able to assist in conveying information as a promotional medium, which can reach more consumers.